Comparative Study of Antifungal Activity of Camellia sinensis and Acacia sinuate Merr against Dandruff Causing Pityrosporum ovale - Kulandhaivel, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe medicinal value of Camellia sinensis and Acacia sinuate Merr were investigated through phytochemical study and in vitro antifungal activity of their various extracts (petroleum ether, chloroform, ethanol and water). The analysis of extracts of the two plants revealed the presence of carbohydrates, saponins, flavanoids, tannins and phenolic compounds. The antifungal activity of Camellia sinensis and Acacia sinuate Merr was tested against dandruff causing Pityrosporum ovale at concentrations of 10, 5 and 2.5 mg/ml assayed by Filter paper disc diffusion technique. The active components present in petroleum ether and ethanolic extracts of Camellia sinensis showed MIC against P. ovale compared to Acacia sinuate Merr in treating dandruff.